Atraumatic spontaneous hemorrhagic cholecystitis. Issue 1 (2nd January 2021) - Rahesh, Jasmin; Payberah, Ebrahim; Anand, Rohan; Ciubuc, John; Athas, Vincent; Brooks, Steven; Ronaghan, Catherine
Abstract: Hemorrhagic cholecystitis is a rare subtype of acute cholecystitis. It is considered a medical emergency, with a morbidity rate of 32% to 58% and a mortality rate of 15% to 20%. It presents with an acute onset of intense abdominal or back pain that can be mistaken for other conditions such as thoracic aortic dissection. Diagnosis hinges on a high index of suspicion and confirmatory studies, such as computed tomography scan or ultrasound. Specific risk factors identified in the literature include a history of trauma and anticoagulant use. We present an atypical case of spontaneous hemorrhagic cholecystitis with no antecedent risk factors.